Front Cover Picture: Bioproduction of Enantiopure (R)‐ and (S)‐2‐Phenylglycinols from Styrenes and Renewable Feedstocks (Adv. Synth. Catal. 7/2021). Issue 7 (16th March 2021) - Sekar, Balaji Sundara; Mao, Jiwei; Lukito, Benedict Ryan; Wang, Zilong; Li, Zhi
Abstract : The front cover picture illustrates whole cells‐based cascade reactions to produce ( R )‐ and ( S )‐2‐phenylglycinols from simple chemicals. Artificial enzyme cascades were developed for the one‐pot green syntheses of ( R )‐ and ( S )‐2‐phenylglycinols from bio‐based L ‐phenylalanine. Natural L ‐phenylalanine biosynthesis pathway was coupled with artificial cascades to directly convert renewable feedstocks such as glucose and glycerol to ( R )‐ and ( S )‐2‐phenylglycinols. Engineering of new artificial enzyme cascades enabled the one‐pot high‐yielding synthesis of several enantiopure 2‐phenylglycinols and 1‐amino‐2‐indanol from simple petrochemicals such as styrenes and indene. Details can be found in the Full Paper by Z. Li and co‐workers (B. S. Sekar, J. Mao, B. R. Lukito, Z. Wang, Z. Li, Adv. Synth. Catal . 2021, 363, 1892–1903; DOI: 10.1002/adsc.202001322 ).